2015
DOI: 10.1007/s10708-015-9620-z
|View full text |Cite
|
Sign up to set email alerts
|

Is better to be a kayayei than to be unemployed: reflecting on the role of head portering in ghana’s informal economy

Abstract: The implementation of neoliberal economic reforms with its resultant effects on rural agricultural economies has facilitated the migration of young girls from northern to southern Ghana to seek for alternative livelihoods in the urban informal economy as head porters (Kayayei). Using semistructured questionnaires and interviews with 45 Kayayei in Makola and Agbogbloshie Markets, Accra, this study examines how migration as a livelihood strategy contributes to an improvement in the living conditions of young gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Case studies in Asia indicate that access to micro-finance enhances women's economic independence and bargaining powers, but the positive impacts are often limited and hindered by a culture of patriarchy pervasive in Asia (Kulkarni, 2011). Similarly, in African countries such as Ghana, women's inability to contribute to household income is due to their weaker financial and social position within society (Agyei, et al, 2016). Therefore, it is argued that access to microfinance, in addition to offering employment, may also improve female psychological and social empowerment (Ganle, et al 2015;Seidu and Bambangi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Case studies in Asia indicate that access to micro-finance enhances women's economic independence and bargaining powers, but the positive impacts are often limited and hindered by a culture of patriarchy pervasive in Asia (Kulkarni, 2011). Similarly, in African countries such as Ghana, women's inability to contribute to household income is due to their weaker financial and social position within society (Agyei, et al, 2016). Therefore, it is argued that access to microfinance, in addition to offering employment, may also improve female psychological and social empowerment (Ganle, et al 2015;Seidu and Bambangi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on kayayei report concerns with the representativeness of their samples (Opare 2003;Yeboah 2010;Addai 2011;Oberhauser and Yeboah 2011;Agyei, Kumi, and Yeboah 2016). To improve representativeness in this study and minimize known sources of nonparticipation bias, the formative research phase discussed past studies' sampling challenges (Table 5) and potential solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The migrants are largely uneducated, unskilled or school drop-outs from rural agricultural communities from the three Northern regions (Upper East, Upper West and Northern). Kumasi, Accra and Sekondi-Takoradi are the most patronized cities for these migrants (Agyei et al, 2016). For consistency, we will stick to 'kayaye' (kayayee, plural).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it can be concluded that, even though females form the majority of migrants for the kayaye business, some male counterparts do also migrate. The records on the population of the Kayayee are lacking as there has been few surveys done on them (Agyei et al, 2016). However their growing presence in the bigger cities gives an indication of their influx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation